CDN modelling with API integration in public information systems of Indonesia: A simulation-based approach - Hendri, Hendri; Hartati, Rukmi Sari; Linawati, Linawati; Wiharta, Dewa Made (Edelweiss Applied Science and Technology, 2025)
This study investigates the integration of Content Delivery Networks (CDNs) and Application Programming Interfaces (APIs) within Indonesia’s public information systems, modelled across the country’s administrative hierarchy. The simulation measures key performance metrics such as Time-to-Live (TTL), Cache Hit Ratio (CHR), Latency, Throughput, and Bandwidth Consumption across five different scenarios. These scenarios involve varying points of origin for content delivery, from the Central Government down to individual villages, reflecting Indonesia’s administrative structure. The study demonstrates that CDN integration significantly improves data delivery efficiency by reducing latency, optimizing bandwidth consumption, and increasing cache effectiveness. These results align with the Indonesian government’s goals of enhancing public information dissemination and supporting digital transformation efforts.